Strategi Pengembangan Sumber Daya Manusia di Bank Syariah: Kunci Untuk Keberlanjutan - Chauzaqi, Farah (Maliki Interdisciplinary Journal, 2025)
The development of human resources (HR) in Islamic banks is a crucial factor in achieving sustainability and competitiveness in the banking industry. Islamic banks need human resources who are not only competent in banking techniques but also have a deep understanding of sharia principles. The main challenges in human resource development in Islamic banks include the lack of sharia competent experts and the high cost of training. This article uses a qualitative method with a literature study approach to identify effective strategies in human resource development. The findings show that continuing education, recruitment of professionals with a background in sharia economics, and systematic career development are important strategic steps. In addition, the implementation of Islamic organizational culture and collaboration with educational institutions are also key in creating superior human resources. With a comprehensive strategy, Islamic banks can improve operational efficiency, product innovation, and customer satisfaction, ultimately strengthening the bank’s reputation and sustainability in a competitive market.